1990
DOI: 10.1073/pnas.87.5.1762
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mice expressing a soluble foreign H-2 class I antigen are tolerant to allogeneic fragments presented by self class I but not to the whole membrane-bound alloantigen.

Abstract: The properties of transmembrane and soluble transplantation antigens were compared with respect to the induction of tolerance and the selection of the T-cell repertoire.For this purpose, transgenic (H-2b X H-2d)F1 mice were constructed that carry integrated copies of a modified H-2Kk gene resulting in the secretion from various cell types including thymocytes of soluble H-2Kk molecules. Despite the presence of H-2Kk antigen, these mice were still able to generate an H-2Kk-specific T-cell response. This respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Previous in vitro studies using T cells from transgenic mice engineered to express a secreted allogeneic MHC class I molecule have shown that alloreactive CTL precursors are able to kill targets through the direct pathway if exogenous IL-2 is present in the cultures even though MHC class I peptide-reactive T cells appear to be absent (22). However, in this study, the effect of expressing a soluble allogeneic MHC class I transgene on allograft survival was not examined.…”
Section: Discussionmentioning
confidence: 54%
“…Previous in vitro studies using T cells from transgenic mice engineered to express a secreted allogeneic MHC class I molecule have shown that alloreactive CTL precursors are able to kill targets through the direct pathway if exogenous IL-2 is present in the cultures even though MHC class I peptide-reactive T cells appear to be absent (22). However, in this study, the effect of expressing a soluble allogeneic MHC class I transgene on allograft survival was not examined.…”
Section: Discussionmentioning
confidence: 54%
“…I. Gentschev, Biozentrum, University Würzburg, Wurzburg, Germany) as a template and was subcloned into pUC19. An XbaI site in front of the ATG start codon was converted to a BamHI site by insertion of a self-complementary oligonucleotide (5Ј-cta gcg gca gga tcc tgc gc-3Ј), then the p60 open reading frame was transferred as a 1.5-kbp BamHI fragment into the vaccinia recombination vector pCS43 (13). Construction of the recombinant vaccinia virus was performed using the vaccinia virus strain Copenhagen and its temperature-sensitive mutant ts7 according to standard procedures as described previously (13).…”
Section: Construction Of Recombinant Vaccinia Virusmentioning
confidence: 99%
“…The generation of a fragment of the correct size was confirmed by gel electrophoresis. The fragment was isolated, cut with BamHI and inserted into the vaccinia virus recombination vector pCS43 (Arnold et al, 1990) downstream of the vaccinia virus early-late promoter p7.5. The correct position of the start codon was confirmed by sequencing of the resulting plasmid pCS43-gH.…”
mentioning
confidence: 99%